Pre-service teachers’ plausibility perceptions of global climate change: The role of cognitive, behavioral and personal variables - Ceylan, Gaye Defne. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
The main purpose of this study was to examine the role of cognitive, behavioral and personal variables on pre-service teachers’ plausibility perceptions of global climate change. The sample of the study was 199 senior pre-service teachers in a public university in Turkey. Five instruments were used to investigate the research questions. Firstly, the participants’ plausibility perceptions of global climate change were investigated. Participants mostly found the items on evidence supporting the human link to global climate change and predictions about future impacts highly plausible. Secondly, the participants’ understanding of global climate change was explored. Although the majority of the participants had an understanding of the human influence on the current climate change and some of the consequences that humans are going to face, the majority of the participants had some misconceptions. Thirdly, correlational analysis showed that there was a significant positive relationship between the participants’ understanding and plausibility perceptions of global climate change. Lastly, the role of cognitive, behavioral and personal variables on plausibility was examined. The results revealed that understanding, degree of willingness to act and need for closure were predictors of plausibility perceptions of global climate change. In particular, understanding had the largest contribution in explaining the variance in plausibility perceptions of the participants. The findings of the current study provide insights for teacher education programs on climate change education.
Keywords: Climate change.; Teachers -- Self-rating of.